HERMENEUTIKA HADIS: Upaya Memecah Kebekuan Teks - Hauqola, Nurkholis (Jurnal THEOLOGIA, 2013)
Abstract: â€œStandardizationâ€ of hadithâ€™ interpretation is a religious understanding manifest Top of Form â€œEstablishmentâ€ in hadith interpretation is a manifesto carries religious understanding entity; not only in the form of interpretation entity, understanding entity, truth entity, Islam entity, but also the other entity in religion. In contemporary lives of people the Prophet hadith presents in a â€œstagnantâ€ and poor application consequently. It ignites a breakthrough to break up the stagnant sphere for shake â€œindigenizationâ€ of the hadith in order to correspond with reality epoch. In hadith interpretation, one of them is hermeneutic approaches. This hermeneutic approach could be achieved using 3 compositions; (1) meaning within the text (internal interpretation of the hadith text, (2) meaning behind the hadith text (things around interpretation of the hadith), (3) meaning in front of the text (â€œthe oppositeâ€ interpretation of the hadith text). These three compositions of the interpretation have focus, target, and method in which are completed one another. They examine not only the horizon of the text (matan), the originator of the horizon (the Prophet), the reader (rijal al-hadith, mukharrij al-hadith, also mufassir), but also its contextuality. Nevertheless, for â€œestablishedâ€ hadith diciplines, hermeneutic is a â€œsupporting instrumentâ€ (not replacing instrument), however, it is perceived able to create interpretation by combining textuality element and hadith contextuality through this hermeneutic approach at once, since a text could only come together in a context. Abstrak: â€œPembakuanâ€ pemaknaan hadis merupakan manifesto pemahaman agama yang mengusung ketunggalan; baik dalam bentuk penafsiran tunggal, pemahaman tunggal, kebenaran tunggal, Islam tunggal, dan ketungalan-ketunggalan lain dalam beragama. Akibatnya, hadis-hadis Nabi hadir di tengah kehidupan umat kekinian dalam bentuknya yang â€œbekuâ€ dan miskin aplikasi. Perihal tersebut memantik terobosan untuk memecah kebekuan demi â€œpribumisasiâ€ hadis agar sesuai dengan realitas zaman. Salah satunya adalah pendekatan hermeneutik dalam penafsiran hadis. Pendekatan hermeneutik dalam penafsiran hadis dapat dilakukan melalui 3 (tiga) lapis penafsiran, yaitu: (1) penafsiran â€œdari dalamâ€ teks hadis (meaning within the text); (2) penafsiran â€œterhadap hal-hal di sekitarâ€ teks hadis (meaning behind the text); dan, (3) penafsiran â€œyang melawanâ€ teks hadis (meaning in front of the text). Ketiga lapis penafsiran ini memiliki fokus, sasaran, serta metode yang antara satu dengan lainnya saling melengkapi. Ia mengkaji bukan hanya horison teks (matan), tetapi juga horison penggagas (Nabi), pembaca (rijal al-hadis, mukharrij al-hadis, serta mufassir), dan kontekstualitasnya. Meskipun hermeneutik merupakan â€œalat bantuâ€ (bukan pengganti) bagi ilmu-ilmu hadis yang telah â€œmapanâ€, namun melalui pendekatan hermeneutik dirasakan mampu melahirkan pemaknaan yang menggabungkan unsur tekstualitas dan kontekstualitas hadis sekaligus, mengingat sebuah teks hanya bisa menemukan maknanya dalam konteks. Kata-kata Kunci: á¸¥adÄ«á¹¡, hermeneutic, textuality, contextualization, interpretation